More dreams of the rarebit fiend: food sensitivity and dietary correlates of sleep and dreaming - Nielsen, Tore; Radke, Jade; Picard-Deland, Claudia; Powell, Russell Arnold (Frontiers in Psychology, 2025)
BackgroundDespite centuries-old beliefs and anecdotal evidence that food can influence one's sleep and dreams—an example being the classic Dream of the Rarebit Fiend cartoon series—the topic has only rarely been researched.MethodsWe asked 1,082 participants to complete an online survey to test specific hypotheses on why people perceive that food affects their dreams, including whether specific foods influence dreams directly (food-specific effects), through physiological symptoms (food distress), or via altered sleep quality (sleep effects). Survey measures included standard demographic variables, targeted probes about self-perceived effects of specific foods on dreams, questions about diet, food intolerances and allergies, personality questionnaires, measures of sleep quality (Pittsburgh Sleep Quality Index) and the Nightmare Disorder Index.ResultsA total of 40.2% of participants reported that certain foods either worsened (24.7%) or improved (20.1%) their sleep, while 5.5% of participants reported that food affected their dreams. The perceived effect of food on dreams was associated with higher nightmare recall and Nightmare Disorder Index scores, with changes being blamed primarily on desserts/sweets (31%) and dairy (22%). The effect was also associated with food allergies and Gluten Intolerance, while worse sleep perceptions were tied to Lactose Intolerance. Nightmare Disorder Index scores were strongly associated with Food Allergy and Lactose Intolerance, the latter being mediated by the severity of gastrointestinal symptoms. Healthy eating, such as less evening eating, predicted higher dream recall, while unhealthy eating—including gastric symptoms, lower reliance on hunger and satiety cues, and evening eating—predicted nightmares and dream negativity.ConclusionsThese results support the food-specific effects, food distress, and sleep effects hypotheses to varying degrees. They replicate associations between diet and dream features, highlighting food sensitivities, particularly Lactose Intolerance, as contributors to nightmare prevalence. Findings open new avenues of research on food-dependent dreaming by suggesting dairy-induced gastrointestinal symptoms as one plausible basis for bizarre or disturbing dreams. They have clear implications for understanding how dietary factors may influence sleep quality and the occurrence of nightmares and could inform non-pharmacological interventions for sleep disturbances.